Kerja Perempuan dan Kebijakan Negara: Kontestasi Perawatan Berbayar dan Tidak Berbayar - Eddyono, Sri Wiyanti (Jurnal Perempuan, 2023)
Paid and unpaid care work has regained prominence in national and international forums as a pivotal issue affecting the low participation of women in development. Despite being predominantly carried out by women, care work remains inadequately recognized and undervalued, especially at the policy level. This paper delves into the reasons behind the lack of attention to care work issues at the national level. It explores the extent of gender ideology implications on state policies related to care work. The research employs desk review and self-reflection based on the author’s experience facilitating discussions on care work issues. The analysis reveals a policy gap in Indonesia concerning care work, influenced by the ambiguity of the state’s gender ideology. Consequently, gender transformation has not been a central focus in care policies, and the legitimacy of women’s roles in unpaid work tends to be reinforced.